2022
DOI: 10.3174/ajnr.a7549
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Collateral Assessment on CTP in the Prediction of Stroke Etiology

Abstract: BACKGROUND AND PURPOSE: Patients with stroke etiology of large-artery atherosclerosis were thought to have better collateral circulation compared with patients with other stroke etiologies. We aimed to investigate the association between stroke etiology and collateral circulation with a new quantitative collateral assessment method. MATERIALS AND METHODS:This retrospective study reviewed data from consecutive patients with proximal anterior artery occlusion who underwent CTP before reperfusion therapy. CBF map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
0
1
Order By: Relevance
“…Clot length may be a simple, fast, and widely available method in the emergency setting. In terms of the CS, a previous study ( 19 ) revealed that collaterals on CT perfusion images showed an excellent ability to identify the stroke classification with an AUC value of 0.87, which is higher than the AUC value observed in the present study. The reason for this discrepancy may lie in the influence of vascular variation, slow blood flow, and leukoaraiosis on the collateral circulation ( 20 ).…”
Section: Discussioncontrasting
confidence: 93%
“…Clot length may be a simple, fast, and widely available method in the emergency setting. In terms of the CS, a previous study ( 19 ) revealed that collaterals on CT perfusion images showed an excellent ability to identify the stroke classification with an AUC value of 0.87, which is higher than the AUC value observed in the present study. The reason for this discrepancy may lie in the influence of vascular variation, slow blood flow, and leukoaraiosis on the collateral circulation ( 20 ).…”
Section: Discussioncontrasting
confidence: 93%